Safety of food workers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Occupational health and safetySafety of food workersThe relevant national authority for legislation on safety, health, hygiene and the working environment for agricultural and food worker is usually located in the ministry dealing with labour...